Value co-creation and innovation performance: A conceptual model - Choo, Ling Suan; Taghizadeh, Seyedeh Khadijeh; Rahman, Syed Abidur (2017)
To expand market share in a dynamic setting of competition, service organizations are obligated to be innovative in offering products and services to its customers. Consequently, Service Dominant Logic (S-D logic) has emerged to involve customers in the process of service development and delivery process which is known as value co-creation.Applying the value co-creation in service development and delivery enables customers to personalize the products and services based on their preferences and desire. This paper contributes in defining and discussing the concept of value co-creation based on DART Model and proposes potential relationships between value co-creation and innovation performance.